THE SOUTH AFRICAN NATIONAL MUSEUM OF MILITARY, HISTORY - Greef, I.B. (Scientia Militaria - South African Journal of Military Studies, 2012)
The South African National Museum of Military History came into being as a result of the Second World War (1939-1945). It was during this period that Captain (later Colonel) J. Agar-Hamilton, official historian of the Union Defence Force, suggested the establishment of a war museum. This was approved by Field Marshal J.C. Smuts who at that time was Minister of Defence and Commander-in-chief of the Union Defence Forces. The Museum was officially opened in its present premises by Smuts on 29 August 1947 and was known as the South African National War Museum until 29 November 1974. The collections of the Museum have been built around a nucleus of objects obtained as a result of the Second World War. This War was truly a global conflict and most of the theatres of the War are portrayed by either objects or displays in the Museum.